Epitope Mapping of the Outer Membrane Protein P5-Homologous Fimbrin Adhesin of Nontypeable Haemophilus influenzae - Novotny, Laura A. (American Society for Microbiology, 2000)
To identify potential immunodominant and/or adhesin binding domains of the outer membrane protein P5-homologous fimbrin adhesin of nontypeable Haemophilus influenzae (NTHI), three sets of synthetic peptides were synthesized and assayed in an adherence inhibition assay, by Western blotting, and in a biomolecular interaction analysis (BIA) system. The first series of 34 8- to 10-mer peptides represented the entire mature protein sequentially. The second set of four peptides (each 19 to 28 residues) represented the four predicted major surface-exposed regions (or loops) of this adhesin. The third series of seven peptides (each 27 to 34 residues) were specifically designed to map the third surface-exposed region. Data obtained by BIA indicated limited reactivity of a panel of high-titered immune chinchilla sera to the 8- to 10-mer peptides representing the mature protein, likely because these linear peptides did not represent continuous epitopes. However, several of these short peptides did inhibit adherence of multiple NTHI strains to a human respiratory epithelial cell. Overall, greatest relative reactivity in both BIA and adherence inhibition assays was demonstrated against, or shown by, peptides mapping to the third and fourth predicted surface-exposed regions of this adhesin, thereby indicating the presence of immunodominant and adhesin binding domains at these sites. Middle ear fluids sequentially recovered from a chinchilla with an ongoing NTHI-induced otitis media (OM) as well as sera from children with OM due to NTHI also reacted exclusively with peptides representing the third and fourth surface-exposed regions of the P5-fimbrin adhesin, indicating a similarity in immune recognition of this bacterial protein by these two hosts. Collectively, these data together with the previously demonstrated protective efficacy of immunogens derived from this adhesin in chinchilla models support the continued development of P5-fimbrin based vaccine components.